Timing of lymphocyte trafficking is regulated by the circadian clock - Morrot, Alexandre (Annals of Translational Medicine, 2017)
Biological systems are composed of a set of genes encoding the synthesis of functional gene products. Their functions can relate to each other in a balanced way to weigh the exact importance of each product at the appropriate time. This dynamic relationship among genes, their functions, time, and the environment is dictated in organisms by endogenous circadian rhythms (1).